2017
DOI: 10.18632/oncotarget.15868
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 R132H mutation regulates glioma chemosensitivity through Nrf2 pathway

Abstract: PurposeNumerous studies have reported that glioma patients with isocitrate dehydrogenase 1(IDH1) R132H mutation are sensitive to temozolomide treatment. However, the mechanism of IDH1 mutations on the chemosensitivity of glioma remains unclear. In this study, we investigated the role and the potential mechanism of Nrf2 in IDH1 R132H-mediated drug resistance.MethodsWild type IDH1 (R132H-WT) and mutant IDH1 (R132H) plasmids were constructed. Stable U87 cells and U251 cells overexpressing IDH1 were generated. Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…Moreover, NADPH is necessary for the synthesis of deoxynucleotides and thus for DNA damage repair [ 58 ]. IDH1/2 mutations cause loss of IDH1/2 wild-type functions [ 28 , 29 ], resulting in decreased NADPH and GSH levels and increased ROS levels, both in steady-state conditions and after induction of ROS production [ 29 , 41 , 48 , 52 , 59 , 60 ]. In addition, d - 2HG accumulation induces oxidative stress independently of IDH1/2 mutations [ 32 34 ].…”
Section: Idh1/2 Enzymes In Redox Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NADPH is necessary for the synthesis of deoxynucleotides and thus for DNA damage repair [ 58 ]. IDH1/2 mutations cause loss of IDH1/2 wild-type functions [ 28 , 29 ], resulting in decreased NADPH and GSH levels and increased ROS levels, both in steady-state conditions and after induction of ROS production [ 29 , 41 , 48 , 52 , 59 , 60 ]. In addition, d - 2HG accumulation induces oxidative stress independently of IDH1/2 mutations [ 32 34 ].…”
Section: Idh1/2 Enzymes In Redox Statesmentioning
confidence: 99%
“…For example, IDH1 mutations induce a gene expression signature that render AML cells vulnerable to all- trans retinoic acid (ATRA/tretinoin), which promotes the expression of genes that induce differentiation of IDH1 -mutated AML cells [ 61 ]. Furthermore, the epigenetic effects of IDH1/2 mutations may underlie many of the synthetic lethalities already described in this review, including the downregulation of NAPRT1 to sensitize cells to NAMPT inhibition [ 52 ], the downregulation of NRF2 and ATM to sensitize cells to chemo/radiotherapy [ 60 , 74 ], the downregulation of BCAT1 to increase the dependency on glutaminolysis [ 90 ], and the induction of homologous recombination defects to sensitize cells to PARP inhibitors, as described above in more detail [ 75 ].…”
Section: Idh1/2 Enzymes In Epigenetic Regulationmentioning
confidence: 99%
“…However, this model has lost 2HG production due to loss of the wild-type IDH allele, a phenomenon that has been shown to occur in IDH mutant gliomas 71 . In contrast, the U87IDHmut model is an easy to grow and very stable model that has been frequently used, not only by our group, but also in several other studies in the literature 7276 . Importantly, we have previously demonstrated that 2HG levels in our U87IDHmut tumor tissue extracts (9.8 ± 1.6 μmol/g of tissue) were comparable to 2HG levels reported in patients (5–35 μmol/g) 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that almost all patients with a malignant glioma receive a single treatment or a combined therapy it is difficult to specify whether IDH1 mutation is associated with a less aggressive phenotype or directly linked to increased sensitivity to therapy. Thus, different studies or clinical trials have been focused on the effect of expression of mutated IDH1 on cellular behavior and response to therapy since the first mutations of IDH1 were discovered in 2008 [17,38,39,40].…”
Section: Introductionmentioning
confidence: 99%